On the crystallography of the Mg–Si–Al nitride nuclei and of the graphite/nitride interface in spheroidal graphite iron. (31st October 2022) - Alonso, G.; Tokarski, T.; Stefanescu, D.M.; Górny, M.; Cios, G.; Suarez, R.
Abstract: The role of Mg–Si–Al nitrides in the nucleation of low-sulfur spheroidal graphite Fe–C–Si alloys has been previously documented. It was demonstrated that when acting as nuclei, in most cases, these nitrides are not singular crystals but are part of complex inclusions. To further document the complexities of this phenomenon a Fe–C–Si melt with 3.55%C and 3.1%Si was treated with a 2.5Ca1.6Zr1.4Al inoculating alloy and poured into a thermal analysis (TA) cup. Samples extracted from the TA cup were analyzed through quantitative optical microscopy. Then, Field Emission Gun Scanning Electron Microscopy was used to identify the nature of the non-metallic inclusions serving as nuclei. It was demonstrated that the main nucleation sites are Mg–Si–Al nitrides that many times nucleate on sulfides. Also, some Ti carbo-nitrides were observed growing on the corners of these nitrides. Further, Selected Area Electron Diffraction techniques provided information on the crystallinity of the nucleus, as well as on the graphite/nucleus interface and on graphite growth in the immediate vicinity of the nitride. Transmission Kikuchi Diffraction patterns suggest that the nitrides are MgSiN2 polycrystals with orthorhombic lattice. Turbostratic graphite was identified in the proximity of the nucleus. It supports a better understanding of the growth of graphite on the nucleating phase and brings some clarity to the ongoing debate on the mechanisms of graphite growth. Graphical abstract: Image 1